Resignation Requirements for Elected Legislative Candidates - Baharuddin Riqiey; Moh. Syahfudin; Firyal Azelia Nasera (Rechtenstudent, 2025)
General elections are one of the indicators that Indonesia is a democratic country, this recognition is strengthened by Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia which emphasizes that sovereignty lies in the hands of the people. In holding general elections, Indonesia faces various challenges, including the phenomenon of the resignation of elected legislative candidates. This action has a negative impact on the health of democracy and causes disappointment among constituents who hope that their representatives can represent their voices in the legislature. In dealing with this problem, a judicial review was carried out at the Constitutional Court regarding Article 426 paragraph (1) letter b of Law No. 7 of 2017, which is the basis for resignation. The Constitutional Court, through Decision Number 176/PUU-XXII/2024, annulled the provision. This annulment provides new hope for democracy in Indonesia, and this study aims to analyze the decision and its implications for the development of the democratic system and the construction of sanctions for political parties that order the resignation of elected legislative candidates. The research findings show that the Constitutional Court, as the guardian of democracy, plays an important role in affirming the sovereignty of the people. If the practice of inappropriate resignation still occurs, sanctions in the form of fines, restrictions on the number of candidates in the next election, and the obligation to take political education can be applied. The imposition of sanctions must still take into account the principles of justice and democracy.